A theory of regime change on the Texas Coastal Plain. (2nd August 2017) - Freeman, Jacob; Hard, Robert J.; Mauldin, Raymond P.
Abstract: The adaptive cycle, a seminal component of resilience theory, is a powerful model that archaeologists use to understand the persistence and transformation of prehistoric societies. In this paper, we argue that resilience theory will have a more enduring explanatory role in archaeology if scholars can build on the initial insights of the adaptive cycle model and create more contextualized hypotheses of social-ecological change. By contextualized hypotheses we mean testable hypotheses that specify: (1) the form of the connections among people and ecological elements and how those connections change; and (2) the resilience-vulnerability tradeoffs associated with changes in the networks and institutions that link social and ecological processes. To develop such a contextualized hypothesis, we combine our knowledge of the prehistory of the Texas Coastal Plain (TCP), mathematical modeling, and the concept of panarchy to study why human societies successfully cope with the interrelated forces of globalization, population growth, and climate change, and, sometimes, fail to cope with these interrelated forces. Our hypothesis is that, in response to population growth, hunter-gatherers on the TCP created increasingly dense social networks that allowed individuals to maintain residual access to important sources of food. While this was a good strategy for individuals to maintain a reliable supply of food in a variable environment, increasingly elaborate social networks created a panarchy of reachable forager-resource systems. The panarchy of forager-resource systems on the TCP created a hidden fragility: The potential for the failure of resources in one system to cascade from system-to-system across the entire TCP. We propose that this occurred around 700 years BP, causing a 6000 year old ritual and mortuary complex to reorganize.